Barron's SAT critical reading workbook - Green, Sharon, 1939-; Weiner, Mitchel, 1907- (Hauppauge, N.Y. : Barron's, 2012)
A workbook for preparing to take the critical reading portion of the SAT that includes hundreds of exercises, with explained answers, as well as tips on building vocabulary.
Young Adult.
Young Adult
Keywords: College entrance achievement tests -- Study guides; Reading comprehension -- Examinations -- Study guides; SAT (Educational test) -- Study guides; Test-taking skills; Universities and colleges -- United States -- Entrance examinations -- Study guides; College entrance achievement tests -- Study guides; Colleges and universities -- United States -- Entrance examinations -- Study guides; Reading comprehension -- Examinations -- Study guides; SAT (Educational test) -- Study guides; Test-taking skills